Mamíferos de la Reserva de la Biosfera “La Sepultura”, Chiapas, México - Espinoza Medinilla, Eduardo (2004)
A species list was elaborated for La Sepultura Biosphere Reserve, Chiapas, Mexico. Line transects and direct observations were made, national and international databases were consulted, and animal traces were registered. Animals were captured during the period May 1994 - December 1999. A total of 848 specimen (248 furs and skulls), 32 tracks in plaster, and 9 osseous fragments were collected. A total of 98 species, 70 genera, 29 families, and 10 orders compose the species list. Of these species 87.7% belong to the orders Chiroptera, Rodentia and Carnivora and 21 species were classified according to some kind of legal protection. These data represent a solid and actualized database useful for designing management and conservation plans for this Biosphere Reserve.